Cinemeducation: An auxiliary tool to traditional teaching learning methods for teaching forensic medicine to undergraduates. - Ravi kanth Soni; Arun Kumar; Mohan Meena; Swapnika Enugala (Mashhad University of Medical Sciences, 2023)
Background: Feature films can be powerful teaching tools and are increasingly used in teaching health sciences. Their power is irresistible as many films consider medical issues. However, there are only few studies which have quantified the effectiveness of using feature films as a method of teaching. Adequate assessment is critical to establish the legitimacy of using the film as a teaching activity.Method: A Quasi-experimental Study was initiated after Ethics Committee approval at Karuna Medical College, Palakkad, Kerala. Informed consent was taken. 90 students were divided into two groups using lottery system. Six movie clips corresponding to the topic were chosen. For one group the topic was delivered through a traditional method and for another group video of the same topic was also shown. Posttest was collected in form of Multiple Choice Questions (MCQ) and crossing over was done. Six sessions were conducted. Fifteen-day memory retention test was conducted for both groups to assess if movies clips helped in student learning and long-term memory retention.Results: A total of 90 students participated. Assessment scores were significantly higher for the groups which were taught using movies along with traditional teaching for 5 out of 6 sessions. It was found that movie clips enhanced learning and long-term memory retention as P value was statistically significant. Most of the participants agreed that movie clips along with the traditional teaching has made their understanding betterConclusion: Cinemeducation is an effective auxiliary tool to traditional teaching learning methods for teaching Forensic Medicine to undergraduates.